Qatar’s genetic counseling landscape: Current insights and future prospects - Abiib, Sumaya (2024)
Genetic counseling is a dynamic and rapidly growing field. In Qatar, the significance of genetic counseling is underscored by the distinctive demographic characteristics of the population, including elevated rates of consanguinity and larger family sizes, contributing to the increased incidence of many genetic conditions. This emphasizes the crucial role of genetic counseling in addressing the specific needs of the community. Over the past decade, key health care institutions in Qatar, such as Hamad Medical Corporation and Sidra Medicine, have significantly expanded genetic counseling services encompassing premarital, reproductive, prenatal, pediatric, adult, and cancer care. This multifaceted approach reflects Qatar’s health care system’s commitment to addressing various aspects of genetic health and well-being across different life stages.A pivotal milestone in the field’s development in Qatar was the establishment of a genetic counseling master’s program at Qatar University in 2018, showcasing the country’s dedication to fostering indigenous expertise in genetic counseling with the necessary competencies and cultural sensitivity to address the unique genetic counseling needs of the population. The recognition of genetic counseling as a profession and the licensure by the Ministry of Public Health in Qatar is another key achievement to ensure the high quality of service and protection of the profession. Contributing to global genetic knowledge, various academic and research entities in Qatar are conducting genetic/genomic/genetic counseling research toward advancing precision medicine in the country, and initiatives such as the Qatar Biobank and Qatar Genome Program have played a major role in catalyzing these efforts.